Direct Anterior versus Anterolateral and Posterolateral Approaches to Total Hip Replacement: Comparative Accuracy of Acetabular Implant Placement and Early Clinical Outcomes - Ying-Lin Chen; Chi-Horng Horng; Yi-Chin Fong; Hsien-Te Chen; Tsung-Li Lin; Chun-Hao Tsai (Formosan Journal of Musculoskeletal Disorders)
Background: Different surgical approaches used in total hip arthroplasty (THA) include direct anterior approach (DAA), anterolateral approach (AL), and posterolateral approach (PL). However, the acetabular cup position varies according to surgical view, surgical table, and patient position for each approach. Objectives: This study is aimed to compare acetabular cup position in THA under different approaches. Materials and Methods: Between Jan 2017 and Dec 2018, 230 patients who underwent THA (64 DAA, 95 AL, and 71 PL THAs) were analyzed retrospectively. Intraoperative blood loss, operation time, preoperative and postoperative WOMAC score, cup anteversion, inclination angle, and postoperative complications were analyzed. Results: DAA showed longer operation time and more blood loss, but shorter hospital stays. The cup was found in the safe zone in 92.2% of the DAA group, 80% of the AL group, and 83.1% of the PL group with Liaw's method; 95.3% of the DAA group, 82.1% of the AL group, and 80.2% of the PL group with Lewinnek's method. PL showed the highest complication rate (9.9%), followed by DAA (3.1%) and AL (1%). Conclusions: THA by DAA using a special table is a more reliable procedure to achieve safe cup position. Although DAA showed fewer outliers in cup position, it resulted in longer operation time and greater blood loss compared to other groups.